Construction of Student Representasi on Three-Dimensional Word Problem - Anwar Muttaqien (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2019)
Many students have difficulty solving the word geometry problem because it requires representation. This study analyzes the construction of representation of class XII students in solving three dimensional word problem. Research with descriptive methods to determine the representation construction that students use when given the task of solving three dimensional word problem. The results showed two constructs of representation, namely: pictorial representation and schematic representation. Students who construct pictorial representations produce correct answers while students who construct schematic representations produce correct answers in solving three-dimensional word problems.